ANALISIS DAN PERANCANGAN SISTEM INFORMASI PEDAGANG PASAR LAMA TANGERANG BERBASIS WEB - Arijanto, Rudy; Fandini, Leona; Angga Mewo, Marcelino; Ando, Ando; Chintia Angel Sirait, Gesima; Putri, Maysha Permata; Rahul Ramadika, Irvan (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2025)
The need for marketing development is very much needed for traditional markets, this is in accordance with the development of online marketing which continues to erode traditional markets. The Old Market traders in Tangerang city were also affected by this. They only rely on traditional sales directly with their buyers. This research offers a solution for how Tangerang Old Market traders can also compete and develop their marketing online with a website built to manage the buying and selling transactions they carry out.